RELEVANSI NILAI INFORMASI AKUNTANSI, SEBELUM ADOPSI IFRS DAN SETELAH ADOPSI IFRS PADA PERUSAHAAN YANG TERCATAT DALAM BURSA EFEK INDONESIA - Kusumo, Yuro Bimo; Subekti, Imam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aimed to explore the value relevance of accounting information in the period before and after the adoption of IFRS in Indonesia . This study uses the value of accounting earnings and book value of equity as a proxy for the value relevance of accounting information . Quality of accounting information can be seen on the relevance of accounting information in the decision-making of investors as reflected in the stock price . Adoption of IFRSÂ -based standards are not predicted to improve the quality of accounting information due toÂ spesific environmental factors in Indonesia . The population of this research is a listed public company on the Indonesia Stock Exchange in the period 2009-2012 . The results showed that the adoption of IFRS -based standards in Indonesia have not been able to improve the quality of accounting information . this is due to only the relevance of equity book value are increased , while the relevance of accounting earnings with investment decisions as reflected in the stock price does not increase significantly in the period after the adoption of IFRS. Keyword: Value relevance, Accounting Earnings, Book Value of Equity, IFRS adoption.